2022
DOI: 10.15678/eber.2022.100106
|View full text |Cite
|
Sign up to set email alerts
|

Impact of market orientation on competitiveness: Analysis of internationalized medium-sized and large enterprises

Abstract: The objective of this article is to identify the impact of market orientation and its elements on company competitiveness of internationalized medium-sized and large enterprises present in Central Eastern Europe and Western Europe in the period of economic growth. Research Design & Methods: Quantitative large sample statistical analysis was conducted on a sample of Hungarian internationalized medium-sized and large enterprises (n=119). Data was obtained by the survey method, the MKTOR scale was implemented in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
(50 reference statements)
0
7
0
3
Order By: Relevance
“…This indicates that variations in competitive advantage of 0.24, or 24%, can be explained by variations in market orientation. The results of this research confirm the findings of previous research, which also found that market orientation has a positive and significant effect on competitive advantage (Maruta et al, 2017;Musigire, 2016;Rahmadi & Dewandaru, 2021;Satwika & Dewi, 2018;Stocker & Várkonyi, 2022).…”
Section: The Effect Of Market Orientation On Competitive Advantagesupporting
confidence: 91%
“…This indicates that variations in competitive advantage of 0.24, or 24%, can be explained by variations in market orientation. The results of this research confirm the findings of previous research, which also found that market orientation has a positive and significant effect on competitive advantage (Maruta et al, 2017;Musigire, 2016;Rahmadi & Dewandaru, 2021;Satwika & Dewi, 2018;Stocker & Várkonyi, 2022).…”
Section: The Effect Of Market Orientation On Competitive Advantagesupporting
confidence: 91%
“…These may be accomplished by using longitudinal and cross-sectional data and quantitative methods. This study’s implications from a policy and societal perspective are relevant because of the importance of IC in contributing to organisational success, specifically during crises and uncertainty – where scholars have suggested the importance of IC and how it may help navigate crises (Verčič et al , 2012), and more importantly, it helps internal knowledge sharing (Stocker and Várkonyi, 2022).…”
Section: Discussion and Study Implicationsmentioning
confidence: 99%
“…For instance, Fonfara et al (2021) measured performance by calculating an arithmetic average of each firm’s market share, sales, profit and return on investment compared to closest competitors. Stocker and Várkonyi (2022) used an index consisting of several objective and subjective measures representing firms’ adaptivity and operationality. Trąpczyński et al (2016) selected five subjective and four objective measures.…”
Section: Understandings Of Central and Eastern European Firms’ Intern...mentioning
confidence: 99%